Fugindo da banalidade: o uso do orkut como extensão da sala de aula - Costa, Adriano Medeiros (2010)
This dissertation investigated the insert and use of the education technologies in the on-line social net Orkut, as an extension of the classroom, especially for debates. With that experience accomplished in a discipline of a Brazilian public institution of higher education, it was tried to go beyond the use of the atmosphere for entertainment and to look Orkut as a tool of assistance to the process of teaching and learning. The research was based in the Paulo Freire´s communication concept and in the Célestin Freinet´s school cooperation concept. In this dissertation, in methodological terms, was adopted the category of the qualitative research. The adopted method was a combination of case´s study with research-action. The technique was the application of questionnaires, the collect of data was personal and the types of data were primary. Finally, introduces, then, prognostics about the future of the on-line social nets and finally suggest the formation of academicals on-line social networks